PELATIHAN HIGIENE DAN SANITASI MAKANAN UNTUK KARYAWAN DI MOMOO JUICE BAR & CAFFE HARBOUR BAY KOTA BATAM - Moh. Thandzir; Haufi Sukmamedian; Syailendra Reza I. R; Natal Olotua Sipayung; Taufik Bachrul Ulum Lubis; Dailami (JURNAL KEKER WISATA, 2024)
Training on food hygiene and sanitation is essential to ensure the safety and quality of food served to consumers. This training usually covers various aspects, such as personal hygiene practices, sanitizing kitchen equipment, safe food storage, and proper cleaning procedures. Typically, this training will cover topics such as: Personal Safety: Personal hygiene practices, such as proper hand washing, wearing clean work clothes, and handling food with clean hands. Sanitizing Equipment and Work Areas: How to clean and maintain kitchen equipment, including cleaning surfaces and work areas to prevent cross-contamination. Maintaining Food Conditions: How to store, process and prepare food to avoid contamination by bacteria or dangerous substances. Waste Management: Actions to safely dispose of waste and minimize the risk of environmental contamination. Food Safety Standards: Understand applicable food safety regulations and standards and the importance of compliance with these regulations.